2018
DOI: 10.1177/1352458517737390
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of probiotics in multiple sclerosis

Abstract: None of the disease-modifying therapies (DMTs) currently being used for the management of multiple sclerosis (MS) are 100% effective. In addition, side effects associated with the use of these DMTs have limited the practice of combination therapy. Hence, there is a need for safe immunomodulatory agents to fine-tune the management of MS. The gut microbiome plays an important role in autoimmunity, and several studies have reported alterations in the gut microbiome of MS patients. Studies in animal model of MS ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 26 publications
5
80
1
Order By: Relevance
“…We show that EAE improvement is associated with an increase in the frequency of T reg cells and with a reduction in the frequency of plasma cells in mice under Lactibiane iki treatment. However, no significant change in the frequency of T reg or plasma cells was observed under Vivomixx treatment, consistent with prior studies in MS patients [17,18]. T reg cells can suppress pathogenic immune responses by reducing or modulating the population of effector T cells mediated through immunosuppressive cytokine secretion or cell-cell interaction [48][49][50].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We show that EAE improvement is associated with an increase in the frequency of T reg cells and with a reduction in the frequency of plasma cells in mice under Lactibiane iki treatment. However, no significant change in the frequency of T reg or plasma cells was observed under Vivomixx treatment, consistent with prior studies in MS patients [17,18]. T reg cells can suppress pathogenic immune responses by reducing or modulating the population of effector T cells mediated through immunosuppressive cytokine secretion or cell-cell interaction [48][49][50].…”
Section: Discussionsupporting
confidence: 88%
“…Regarding Bifidobacteria, probiotics composed of different strains including Bifidobacterium have exhibited beneficial effects in EAE [11,69] and MS [17,18] and have been correlated with anti-inflammatory immune markers. Concerning Vivomixx, composed by genera Lactobacillus, Bifidobacterium, and Streptococcus, the observed increase in the genus Streptococcus (family Streptococcaceae) is consistent with probiotic composition, with prior studies in Vivomixx-treated MS patients, and connected to anti-inflammatory responses affecting mainly DCs and monocytes [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This beneficial effect was IL‐10 dependent, and treatment with Lactobacilli induced Treg cells in the mesenteric lymph nodes, but also in the periphery. A pilot study in humans demonstrated the relevance of probiotics as immunomodulatory agents in patients with MS and healthy controls . Administration of VSL3, a probiotic cocktail of eight bacteria, induced changes in the gut microbiota composition that were associated with anti‐inflammatory immune responses in the periphery.…”
Section: Probiotics and Gut Microbiota‐derived Tryptophan Metabolitesmentioning
confidence: 99%
“…In addition, treatment of MS by probiotic VSL3 induces enrichment of specific microbial species in intestine and inhibits peripheral monocyte-mediated inflammation [43]. EECs indeed express receptors that recognize SCFAs [44], which are produced at an elevated rate through the fermentation of fiber by gut microbiota.…”
Section: Enteroendocrine Cellsmentioning
confidence: 99%